Mechanism of dislocation channel-induced irradiation assisted stress corrosion crack initiation in austenitic stainless steel. Issue 5 (October 2015) - McMurtrey, M.D.; Cui, B.; Robertson, I.; Farkas, D.; Was, G.S.
Highlights: Three classes of dislocation channel–grain boundary intersections were observed. Discontinuous channels undergo the least amount of displacement. Discontinuous channels cause the greatest amount of stress at the grain boundary. Discontinuous channels are the most likely to induce crack initiation. IASCC is due to these high levels of stress at the channel–boundary intersection. Abstract: The mechanism by which dislocation channeling induces irradiation assisted stress corrosion cracking was determined using Fe–13Cr15Ni austenitic stainless steel irradiated with protons to a dose of 5 dpa and strained at high temperature in both argon and simulated boiling water reactor normal water chemistry environments. Straining induced dislocation channels that were characterized by digital image correlation and confocal microscopy. Dislocation channels were found to be either continuous across the boundary, discontinuous, or discontinuous with slip in the boundary. Discontinuous channels were found to contain the least amount of strain but have the highest propensity for initiating cracks. Discontinuous dislocation channel–grain boundary intersections were shown to have the highest local stress. TEM in-situ straining of irradiated steels and atomistic simulation of dislocation–grain boundary interaction provided supporting evidence that channels that were unable to transfer strain underwent cracking. The inability of channels to relieve stress, by either slip in the adjacent grain or in the grain boundary, resulted in high local stresses and increased susceptibility to stress corrosion cracking initiation.